Correction of Flexural Deformity of the Metacarpophalangeal Joint in a Calf - Compagnoni, Isabelle Smaniotto; Gomes, Anny Raissa Carolini; Becker, Ana Paula Brenner Busch; Rossa, Ana Paula; Strugava, Lucimara; Brum, Juliana Sperotto; Moreno, Juan Carlos Duque; Dornbusch, Peterson Triches (Acta Scientiae Veterinariae, 2022)
Background: The congenital flexural deformity is common in cattle, often affecting the metacarpophalangeal joint of the thoracic limbs. The deformity may be mild, moderate, or severe, and the therapy depends on the limb's degree of flexion and the affected joint. In severe deformities, tenotomy of the flexor tendons and desmotomy of the suspensor ligament is recommended. However, this surgical technique may not be sufficient to promote limb extension, and other interventions may be necessary. Thus, the purpose of this report is to describe a technique to correct severe flexural deformities of the metacarpophalangeal joint in calves. Case: A three-month-old, female, Dutch-bred calf weighing 46 kg was referred for treatment of congenital flexural deformity. On attendance, the patient presented severe deformity in the right thoracic limb and mild in the left thoracic limb both at the height of the metacarpophalangeal joints. During palpation it was possible to notice that the flexor tendons were contracted in both limbs. Radiographic exams were performed to rule out the presence of other diseases, confirming the diagnosis of flexural deformity. The patient was referred to surgery to correct the anatomical anomaly. The animal was submitted to general anesthesia and placed in right lateral decubitus. In the left thoracic limb, an incision was made in the medial region of the metacarpal bone, the tissues were divulsioned until the superficial digital and deep digital flexor tendons were exposed; these structures were sectioned with a scalpel, and the limb was extended, returning to the standard anatomical position. In the right thoracic limb, the same procedure was performed, but during the limb extension test, we observed that the limb remained flexed, we then followed with a second incision and section of the deep digital flexor tendon in the palmar region at the middle phalanx of the lateral and medial digits, with this procedure, the limb extended further. Nevertheless, the procedure was not enough to solve the problem in the right thoracic limb, and the patient needed a second surgical intervention, in which we performed again tenotomy of the flexor tendons and desmotomy of the digital annular, crossed sesamoid, and interdigital phalangiosamoid ligaments, associated to the capsule opening of the capsule from the affected right metacarpophalangeal joint. After this surgery, the patient recovered to the normal anatomical position of the right thoracic limb. The procedures were efficient in achieving the normality of both affected limbs, and the patient recovered without postoperative complications. Discussion: In severe flexural deformities of the metacarpophalangeal joint in bovines, the fetlock's flexor tendons and suspensory ligament are implicated in the limb contracture. For these cases the chosen treatment is surgery with sequential sectioning of the flexor tendons and the suspensory ligament until the extension of the flexed limb occurs. Although there are reports that confirm the efficacy of this technique, there are cases in which other anatomic structures are involved in the limb contracture. In addition, the desmotomy and tenotomy techniques are not enough to achieve the normality of the affected joint, with the limb remaining flexed, leading to euthanasia of the patient in some cases. In cattle, few reports demonstrate possible techniques for severe contractures of the metacarpophalangeal joint, requiring further studies and new techniques to achieve recovery of these patients. Keywords: bovine, congenital, anatomical anomaly, contracture, tendon, fetlock. Descritores: bovinos, congênita, anomalia anatômica, contratura, tendão, boleto. Título: Correção de deformidade flexural da articulação metacarpofalangeana em uma bezerra